Chapter L’invention d’une «tradition» liturgique: le rite de consécration des princes valaques (XVIIe-XVIIIe siècles) - Radu G., Păun (Firenze University Press, 2025)
The aim of this study is to re-examine the question of the alleged Byzantine origin of the consecration ritual of the Wallachian princes and to reconstruct the liturgical scenario and the political context in which this ritual emerged. The first part provides an overview of the sources on the coronation of Byzantine emperors. The second part outlines the liturgical tradition of the coronation of monarchs in the South Slavic countries (Bulgarian and Serbian states). The third part aims at reconstructing the liturgical scenario of the consecration of the Wallachian princes, taking into account the main elements of the ritual, notably the liturgical gestures and words, but also the spatial dimension of the ceremony, i.e. the place where the liturgical act was performed. A thorough analysis of the sources shows that, contrary to common opinion, this scenario has nothing in common with the rite of the consecration of the basileis, but was inspired by and closely follows the rite of episcopal ordination as it appears in the Archieratikon. The theological-political significance of this choice is analyzed in the fourth and final part of the study. Finally, this study is accompanied by a documentary portfolio (originals and translations).